2016
DOI: 10.1039/c5nj02894a
|View full text |Cite
|
Sign up to set email alerts
|

CdS/ZnIn2S4/TiO2 3D-heterostructures and their photoelectrochemical properties

Abstract: We describe the synthesis and application of a three-dimensionally (3D) structured CdS quantum dot / ZnIn 2 S 4 nanosheet / TiO 2 nanotube array (CdS/ZnIn 2 S 4 /TiO 2 ) heterostructured material architecture. TiO 2 nanotube arrays (TiO 2 NTAs) are used as the synthetic template, subsequently sensitized using hydrothermal and successive ion layer adsorption and reaction (SILAR) techniques. The described synthesis approach offers a powerful technique for designing 3D heterostructure systems.Under AM1.5G illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…These structures are called ternary metal chalcogenides. From among the family of AB2S4 semiconductors, ZnIn2S4 is the only member with a layered structure (see Figure 1b) [62]. It is a potentially visible-light-responsive photocatalyst reported with three different polymorphs, including, cubic, hexagonal and rhombohedral phase [63].…”
Section: Crystalline Structures Of Sulfide Based Photocatalystsmentioning
confidence: 99%
“…These structures are called ternary metal chalcogenides. From among the family of AB2S4 semiconductors, ZnIn2S4 is the only member with a layered structure (see Figure 1b) [62]. It is a potentially visible-light-responsive photocatalyst reported with three different polymorphs, including, cubic, hexagonal and rhombohedral phase [63].…”
Section: Crystalline Structures Of Sulfide Based Photocatalystsmentioning
confidence: 99%
“…The valid h + /e − pairs afterwards could react with H 2 O and O 2 in an aqueous solution (Equations ( 1)-( 7)) to produce reactive species. As it is known, the generated hydroxyl radical (•OH) species can be used as a strong oxidizer for the non-selective killing of bacteria [37]. The amount of •OH is detected by the fluorescent intensity of 2-hydroxyterephthalic acid (λ = 420 nm) which is a product of the reaction of •OH with terephthalic acid [38].…”
Section: Antibacterial Mechanismmentioning
confidence: 99%
“…However, TiO 2 is active only under near-ultraviolet irradiation, only around 4% of the incident solar spectrum energy, due to its wide band gap energy of 3.0-3.2 eV. 4,5 Numerous attempts were made to extend the light absorption of TiO 2 to the visible light range, which accounts for around 48% of the incident solar energy. 6 Fe 2 O 3 is considered to be one of the best co-catalyst candidates due to its appropriate band gap (E g $ 2.2 eV) for solar light harvesting, good photochemical stability, earth abundance, nontoxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that co-sensitizing TiO 2 with different nanocrystals such as CdS/ZnIn 2 S 4 , 4 CdTe/Mn-CdS, 12 CdS-Mn/MoS 2 /CdTe, 13 CdS/CuInS 2 /Au, 14 Mn-CdS/MoS 2 , 15 and CdS-based photocatalysts [16][17][18] can extend the light absorption to the infrared range, and more importantly align the energy bands of the semiconductor. In summary, combining TiO 2 with Fe 2 O 3 and CdS semiconductors could largely improve the photocatalytic activity of the co-sensitized electrode, as the energy levels of Fe 2 O 3 (bandgap $2.2 eV), CdS ($2.4 eV), and TiO 2 (3.0-3.2 eV) are well suitable to one another, which benets the separation of e À -h + pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation